Stakeholders' views on effective employment support strategies for autistic university students and graduates entering the world of work. Issue 1 (7th April 2021) - Pesonen, Henri; Waltz, Mitzi; Fabri, Marc; Syurina, Elena; Krückels, Sarah; Algner, Mona; Monthubert, Bertrand; Lorenz, Timo
Abstract : Purpose: This paper aims to examine effective support strategies for facilitating the employment of autistic students and graduates by answering the following research question: What constitutes effective employment support for autistic students and graduates? Design/methodology/approach: Data were collected using the method of empathy-based stories (MEBS) as part of a multinational European project's Web-based survey. The data consisted of 55 writings about effective strategies and 55 writings about strategies to ]avoid when working with autistic students and graduates. The material was analysed using qualitative inductive content analysis. Narratives were created to illustrate desirable and undesirable environments and processes as they would be experienced by students, supported by original excerpts from the stories. Findings: The analysis revealed that effective employment support for autistic students and graduates comprised three dimensions of support activity: practices based on the form and environment of support, social interaction support and autism acceptance and awareness. These dimensions were present in both recommended and not recommended support strategy writings. Originality/value: The results add to the literature on autism and employment with its focus on the novel context of autistic university students and graduates. Effective strategies will be based on person-centred planning, to include not only the individual impact of autism but also individual career goals, workplace characteristics in the chosen field, employer needs and allocation of the right support. There is no one-size-fits-all strategy, but rather an individualized process is needed, focused on the identification of strengths, the adaptation of employment and work processes and improved understanding and acceptance of autism by management, colleagues and administration in the workplace.